Connecting Top-Down and Bottom-Up Approaches in Environmental Observing. (28th April 2021) - Eicken, Hajo; Danielsen, Finn; Sam, Josephine-Mary; Fidel, Maryann; Johnson, Noor; Poulsen, Michael K; Lee, Olivia A; Spellman, Katie V; Iversen, Lisbeth; Pulsifer, Peter; Enghoff, Martin
Abstract: Effective responses to rapid environmental change rely on observations to inform planning and decision-making. Reviewing literature from 124 programs across the globe and analyzing survey data for 30 Arctic community-based monitoring programs, we compare top-down, large-scale program driven approaches with bottom-up approaches initiated and steered at the community level. Connecting these two approaches and linking to Indigenous and local knowledge yields benefits including improved information products and enhanced observing program efficiency and sustainability. We identify core principles central to such improved links: matching observing program aims, scales, and ability to act on information; matching observing program and community priorities; fostering compatibility in observing methodology and data management; respect of Indigenous intellectual property rights and the implementation of free, prior, and informed consent; creating sufficient organizational support structures; and ensuring sustained community members' commitment. Interventions to overcome challenges in adhering to these principles are discussed.